What's New in Ocular Drug Delivery: Advances in Suprachoroidal Injection since 2023 - Kevin Y. Wu; Angel Gao; Michel Giunta; Simon D. Tran (MDPI AG, 2024)
Despite significant advancements in ocular drug delivery, challenges persist in treating posterior segment diseases like macular edema (ME) and age-related macular degeneration (AMD). Suprachoroidal (SC) injections are a promising new method for targeted drug delivery to the posterior segment of the eye, providing direct access to the choroid and retina while minimizing systemic exposure and side effects. This review examines the anatomical and physiological foundations of the SC space; evaluates delivery devices such as microcatheters, hypodermic needles, and microneedles; and discusses pharmacokinetic principles. Additionally, advancements in gene delivery through SC injections are explored, emphasizing their potential to transform ocular disease management. This review also highlights clinical applications in treating macular edema, diabetic macular edema, age-related macular degeneration, choroidal melanoma, and glaucoma. Overall, SC injections are emerging as a promising novel route for administering ophthalmic treatments, with high bioavailability, reduced systemic exposure, and favorable safety profiles. Key therapeutic agents such as triamcinolone acetonide, dexamethasone, AAV-based gene therapy, and axitinib have shown promise. The field of suprachoroidal injection is progressing rapidly, and this review article, while attempting to encapsulate most of the published preclinical and clinical studies, mainly focuses on those that are published within 2023 and 2024.